Physical property response of peri-well sediments during cementing of gas hydrate-bearing sediments in conventional oil-gas wells in the South China Sea - Wang, Xiaoyu; Zheng, Mingming; Zhou, Kerui; Qi, Qiaomu; Wu, Zurui; Yan, Shichun; Zeng, Guoao; Ma, Ting (Frontiers in Earth Science, 2023)
When deep-water oil-gas cementing encounters natural gas hydrate bearing sediments, gas hydrate in sediments near the wellbore is often decomposed to high pressure free gas and water due to hydration and exothermic of cement slurry, causing mechanical damage to the sediment and affecting the quality of well cementing, even leading to cementing scrapping, resulting in serious engineering accidents and economic losses. In this study, gas hydrate bearing sediments in Shenhu Area of the South China Sea is taken as the research object, numerical simulation software TOUGH+HYDRATE is used to realistically reproduce the process of cement slurry exothermic and penetration by "continuous segmental simulation". The physical properties response of sediments near the well wall during cementing under different cementing process parameters and sediment geological parameters are well studied. Results show that the hydration exothermic rate of cement slurry has significant influence on the decomposition degree of hydrate in the penetration area, when it is higher than 0.21 J·(g·s)-1, the hydrate in the penetration range is completely decomposed. The cementing pressure difference affects the cement slurry penetration depth, the extent of sediment pressurization and heat-up, which in turn affects the range of the decomposition zones. Extending the holding time of cementing pressure difference expands the heat-up and decomposition zones, but also delays the onset of hydrate decomposition. Higher saturation prevents the penetration of cement slurry and weakens the diffusion of pore pressure, which causes the shrinkage of the heat-up and decomposition zones, and makes higher pressure in the decomposition zone. The hydrate phase equilibrium environment directly determines the resistance of hydrate sediments to perturbation, with insignificant changes in physical properties in stable sediments. The permeability affects the transport efficiency of pore fluid and expands the heat-up zone and decomposition zone, but also weakens the pore pressure peak of sediment. The porosity affects the sediment pore volume and the penetration volume of cement slurry, and with less significant effects on the extent of sediment pressurization, heat-up, and hydrate decomposition.